MAKNA SIMBOLIK SUNDA WIWITAN DALAM TRADISI MEUNGKEUT BUMI - Yayang Dwi; Ranti Pebrianti Ranti; Dede Fatimah Deffa; Zikri Fachrul Nurhadi (Commed Jurnal Komunikasi dan Media, 2023)
This research is motivated by problems from culture in the beliefs of Sunda Wiwitan which require the existence of the "Meungkeut Bumi" tradition in the pre-marital process. The research method used in this research is descriptive research method with a qualitative approach and data collection is done through participant observation, in-depth interviews, literature studies and documentation. The theory used in this study is the ethnographic theory by Prof. Engkus Kusworno, communication ethnography is a theory that examines the role of language in communicative behavior in different societies. The theoretical assumptions include speech communities, communication activities, communication components, communication competencies and language varieties. The results of this study explain that "Sunda Wiwitan's Symbolic Meaning in the Mengkeut Bumi Tradition" is a procession which means uniting two women and men by tying a yellow and white shawl which also means that they have made promises to each other to step into marriage. The color on the yellow shawl means wind and the white shawl means water. Sunda Wiwitan is a sect adhered to by the indigenous Sundanese people or the original Sundanese religion. The Sunda Wiwitan community is spread across West Java, one of which is in Kampung Pasir, Cintakarya Village, Samarang District, Garut Regency.